Clinical significance of the buccal fat pad: how to determine the correct surgical indications based on preoperative analysis - Tarallo, Mauro; Fallico, Nefer; Maccioni, Francesca; Bencardino, Davide; Monarca, Cristiano; Ribuffo, Diego; Taranto, Giuseppe Di (International Surgery Journal, 2018)
Background: Despite the multitude of clinical and aesthetic uses, the correct surgical indications for buccal fat pad (BFP) removal have yet to be fully elucidated. Although the procedure is widely performed and promoted for aesthetic purpose, literature lacks of studies accounting for a proper evaluation of patients undergoing BFP removal. Methods: Between 2012 and 2016 patients seeking an improvement of the malar contour by reduction of the submalar prominence have been visited at the Department of Plastic Surgery of the Institution. A preoperative MRI was requested in order to correctly identify the volume of the BFP and the presence of a masseter muscle (MM) hypertrophy. Results: According to clinical examination and the results of the preoperative imaging, patients were offered different treatment options: patients with BFP hypertrophy underwent BFP removal through an itraoral approach; patients with MM hypertrophy received injection of 50 UI of botulinum toxin (BTX). No complications were observed in the postoperative period and all patients were satisfied with the results. Conclusions: According to the experience, midface contouring procedures should take account of both surgeons’ experience, patients’ expectations and anatomical evaluation. As such, there is no given approach suitable for all cases. Suggested visual criteria, clinical examination and imaging analysis are useful in establishing patient’s condition and determining the appropriate methods of treatment to enhance the facial profile.